Kontestasi Kepublikan Antara Sektor Publik dan Swasta pada Pertanian Jagung di Kabupaten Bantul - Alfiana, Alfiana; Orie Rahma, Erythina; Ramadhan Wahfianka, Ega (Policy, Law and Political Research Center, 2023)
One of the sectors that support the country's largest economy is the agricultural sector. Bantul Regency is one of the regencies in the Special Region of Yogyakarta which makes agriculture one of the leading sectors in increasing GRDP. In the corn farming sector in the Bantul district, there is private sector involvement, namely Syngenta, which is the alternative choice of residents in the corn farming development process. The involvement of the private sector undermines the public value that the government should play. This study aims to analyze the contestation that occurs between Syngenta and public actors in agricultural management through the theory of organizational representation by Guo & Musso (2007) in realizing public value through mapping organizational legitimacy and organizational capacity. Researchers used qualitative methods with a hermeneutic approach. Researchers collected data through observation, focus group discussion, and secondary data studies. The results showed that there was a struggle for the public arena in agricultural management in Bantul Regency. In fact, it seems that the public sector has been won by the private sector rather than the government, which has to 'under-deliberate' with local farmers. It is feared that the continuation of this phenomenon over a relatively long period of time will disrupt the legitimacy of the government.